Joakim, Uzziah, and Bagoas : a literary analysis of selected secondary characters in the Book of Judith - Branch, Robin Gallaher (Old Testament essays, 2012)
Secondary characters in any literary work play supporting roles. In their cameo appearances, they reinforce the importance of the primary characters, the stars. While not given top billing, they nonetheless remain crucial to the plot and contribute to its twists and turns. When a secondary character interacts with a primary character, additional traits of the primary character emerge. However in this interaction, often distinct personality traits of the secondary character likewise appear. This article looks at selected secondary characters in the Book of Judith: Joakim, the high priest and leader of the council in Jerusalem; Uzziah, the magistrate of Bethulia, the city besieged by Holofernes and the Assyrian army; and the Bagoas, Holofernes' aide decamp. Via a literary approach which sees Judith as a fictional short story, this article examines the contributions of selected characters who play supporting roles to Judith, the beautiful Bethulian, and Holofernes, the Assyrian general who ignominiously dies by her hand.